2020
DOI: 10.5588/ijtld.20.0172
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of asthma treatment guidelines and Essential Medicine Lists in sub-Saharan Africa

Abstract: INTRODUCTION: Asthma is a chronic condition affecting between 300 and 400 million people worldwide. Studies have shown that asthma symptoms can be controlled by the daily use of inhaled corticosteroids (ICS). The management of asthma varies in different settings.METHODS: Asthma management in 13 sub-Saharan African countries was compared to the 2018 Global Initiative for Asthma (GINA) guidelines and the 20th WHO model list of essential medicines (2019). A table with predefined criteria extracted from the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…23 The use of oral medicines, either oral SABA or theophylline, might be a consequence of unavailability or unaffordability of inhaled asthma medicines in some countries. 25 Among children and adolescents, we observed a significant association between use of any oral medication and being in UMICs or LMICs and LICs. However, in HICs, where availability of inhaled medicines should not be a consideration, theophylline was being used in about one in ten adolescents and adults with severe symptoms, indicating other influences beyond economic factors.…”
Section: Discussionmentioning
confidence: 71%
“…23 The use of oral medicines, either oral SABA or theophylline, might be a consequence of unavailability or unaffordability of inhaled asthma medicines in some countries. 25 Among children and adolescents, we observed a significant association between use of any oral medication and being in UMICs or LMICs and LICs. However, in HICs, where availability of inhaled medicines should not be a consideration, theophylline was being used in about one in ten adolescents and adults with severe symptoms, indicating other influences beyond economic factors.…”
Section: Discussionmentioning
confidence: 71%
“…Lack of affordability and access to appropriate inhaled asthma therapy remains a major challenge [ 73 ]. An analysis of asthma management in 13 sub-Saharan African countries found that only 46% and 38% had inhaled corticosteroids at a primary- and secondary-level health facility, respectively [ 103 ].…”
Section: The African Situationmentioning
confidence: 99%